PENGARUH BAHAN ORGANIK TERHADAP POPULASI Aspergillus flavus PADA BEBERAPA JENIS TANAH - Sudadi; Endang Setyorini (Sains Tanah: Journal of Soil Science and Agroclimatology, 2002)
The objective of the research was to study the effect of soil type and organic matters applied on the growth of innoculated Aspergillus flavus. Considering the caracteristics of soil and organic matter source types, the organic carbon content total nitrogen content. C/N ratio and pH of the soil were analized. The research design used was completely randomized block design with two factors, namely soil type (regosol, grumosol and latosol) and organik matters applied (control; manure and straw). Treatment replication was considered as variation source of block. It was indicated that there was signcant effect (P < 0,05) of soil type on the growth of the fungsi. Latosol tended to give higher growth than regosol and grumosol. Though no significant effect of organics matters indicated, the fungsi showed better growth with application of straw. It seemed the result had nothing to do with the carbon and nitrogen content of the soil. They might be caused by other factors that should be studied further.